FRAGMENTE AUS DAVIDS PSALMEN. MUSIKALISCHE FORSCHUNGEN - Mihai BRIE (Studia Universitatis Babeş-Bolyai. Musica, 2020)
In multidisciplinary research, theology and musicology occupy a special place. In the present scientific research we have corroborated historical data about Jewish Palestine, with special reference to one of the books of the Old Testament, the Psalms of David. In the present academic incursion I proposed a musicological-theological vision regarding one of the most special publications, the psalms. The psalm par excellence is a hymn of adoration, thanksgiving and prayer that the Christian addresses to God.